Information use of software packages in Nigerian university libraries (2011)
The use of two library software in managing information in four Nigerian university libraries was investigated. The study population comprised 56 library staff and 234 undergraduates who were library users and data was collected using questionnaire and interview. Library staff in all the libraries revealed that ease of use, user friendliness, availability of system manual were the major software selection factors used. Cataloguing module was used the highest on a daily basis by the staff in all the libraries while the undergraduates used the OPAC mostly on a daily basis in University of Lagos and Covenant University (57.4% and 54.7%) respectively. Problems such as occasional system failure, erratic power supply, inadequate training facilities and network problem hindered the maximum use of the software by library staff, while inadequate orientation on their use which resulted in difficulty in its use were the problems encountered by the undergraduates. The library software have been useful to both library staff and undergraduates but training and re-training of library personnel, adequate orientation of users and provision of sufficient computer systems at OPAC section of the libraries would enhance their use.